KONTRIBUSI PENDAPATAN PETANI KARET, SAWIT DAN PALAWIJA TERHADAP PENDAPATAN KELUARGA PETANI DI DESA SIMPANG JAYA KECAMATAN WANARAYA KABUPATEN BARITO KUALA KALIMANTAN SELATAN - Idah Fitriani; Muhammad Helmi; Daniel Itta (Universitas Lambung Mangkurat, 2020)
This study was conducted to determine the value of the contribution of rubber, oil palm and secondary crops to the income of farm families in Simpang Jaya Village, Wanaraya District, Barito Kuala Regency, South Kalimantan. This research is also used to find out the supporting and inhibiting factors in rubber, palm oil and pulses farming in Simpang Jaya Village, Wanaraya District, Barito Kuala Regency, South Kalimantan. This study uses a purposive sampling method that is intentional sampling in accordance with the required sample requirements (certain people) according to the nature, characteristics, characteristics, and criteria. So that researchers can judge for themselves who deserve to be respondents. The results of the contribution of rubber, oil palm and secondary crops to the family income of the farmers obtained the value of the contribution of rubber farmers by 47.57%, while the contribution of oil palm farming by 27.70%, and the contribution of the secondary agricultural business by 24.73%.Keywords: contributions, family income farmers